Diagnostic and systematic significance of petiole anatomy in the identification of Hopea species (Dipterocarpaceae) - Norhana Nabila, Mohamed Talip; Cutler, David F.; Aida Shafreena, Ahmad Puad; Ismail, B. S.; Ruzi, A. R.; Ahmad Juhari, A. A. (Elsevier B.V., 2017)
A comprehensive study of the petiole anatomy of 33 species of the genus Hopea Roxb., belonging to the family Dipterocarpaceae, was carried out to examine variations in the petiole anatomy that might be useful in the identification and classification of the various species. The variations observed included the petiole outline, vascular bundle arrangement, trichome types, number of resin canals and presence of cell inclusions. Findings have shown that petiole anatomical characteristics are of taxonomic value for this genus and are valuable for species identification and classification. A combination of different petiole outlines and types of vascular bundle arrangement enable the division of this genus into five distinguishable groups. Variations in trichome types, distribution of sclerenchyma and resin canals provide useful diagnostic characters. In general, the petiole characteristics observed in the present study did show, to some extent, relationships in the context of existing phylogenies, but the findings cannot be used for the identification of Hopea species and more anatomical characteristics are needed for this purpose.